Emergency remote teaching, students' motivation and satisfaction of their basic psychological needs in higher education - Lepinoy, Anouk; Vanderlinde, Ruben; Lo Bue, Salvatore (Frontiers in Education, 2023)
Introduction The first part of the worldwide lockdown starting in March 2020 forced teachers in higher education to implement emergency remote teaching (ERT) in an online learning environment. Some students appreciated the autonomy they acquired and the appeal to their self-discipline. Other students, preferring structure and guidelines, perceived these new learning circumstances as ambiguous and unclear. Pressing circumstances, such as a pandemic forcing students into a new learning environment, pose a challenge to their academic motivation. On that premise, this study suggests that the sudden change of learning environment following ERT report an impact on the fulfillment of the basic psychological needs of learners and consequently, on their motivation. More concretely, we hypothesized that this new learning environment had a demotivating effect on students' motivation. The central question in this research is therefore “To what extent did students' motivation shift with ERT.” Methods This embedded mixed method study, where one dataset (qualitative) plays a secondary role in a study that is primarily based on the other dataset (quantitative), consists of two measurement points: academic motivation was measured among students from the Royal Military Academy (RMA), before the WHO's declaration of the pandemic (T1, December 2019) and during the pandemic (T2, June 2020). To measure autonomous motivation, we used the Learning Self-Regulation Questionnaire (SRQ-L). To measure satisfaction and frustration for autonomy, relatedness, and competence, we used the Psychological Needs Satisfaction and Frustration Scale (BPNSFP). To identify new issues not captured in the closed questions, the survey at T2 included a qualitative second part with one open-ended question. Results When comparing pre-pandemic to pandemic academic motivation results by a repeated-measure analysis, we found that the first college year students' motivation was the most negatively affected, followed by that of the second college year students. In addition, by using a multiple regression, we found that ERT affected perceived competence suggesting that lower perceived competence contributes to a lower academic motivation. Discussion Based on these results, this study underlines the importance of assessing learners' sense of competence before immersing them into an online learning environment or changing their learning environment in any other way. This study implies that higher education teachers should provide students with the necessary knowledge to use self-regulatory strategies, encourage self-discipline to improve learning outcomes and endorse a role of helpful coach with the possibility of interaction. By doing so, higher education teachers can meet students' basic needs and can keep autonomous motivation as high as possible among learners. This study adds to the literature insights that can help to optimize educational practices and set up classroom-wide interventions during teacher training so that teachers can facilitate these skills among their students.